(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Posterior Reversible Encephalopathy Syndrome (PRES) is a clinical-radiological condition that is generally reversible. However, a significant number of patients may experience permanent neurological sequelae, which can lead to a fatal outcome. The study aimed to find out the various causes, clinical symptoms, and imaging results of patients with PRES. It also aimed to understand how these factors are related to the patients’ clinical outcomes. Materials and methods: This prospective observational study comprised of 56 patients who fulfilled the criteria for the diagnosis of PRES from the Department of Neurology, Medicine, Gynae & Obstetric of Chittagong Medical College Hospital. The demographic and clinical data, imaging findings, and laboratory parameter were duly recorded.Patients’ outcomes were assessed using modified Rankin Scale (mRS) scores one month after the initial symptoms of PRES. Results: The mean age was 24.4±9.6 years and 91.1% were female. The most common symptoms were seizure (98.2%), headache (78.6%), blurred vision (60.7%), stupor (51.8%) and vomiting (41.1%). The most frequent precipitating cause was posttpartum pre-eclampsia / eclampsia (53.6%), followed by antepartum pre-eclampsia / eclampsia (30.4%), acute HTN (10.4%) and acute kidney injury (5.4%). The parieto-occipital region was the most common area of involvement (98.2%), followed by the frontal lobe/superior frontal sulcus (75%), temporal (51.8%), holohemispheric watershed (26.8%), cerebellum (10.7%), basal ganglia (8.9%) and brainstem (1.8%). Haemorrhage was seen rarely (7.2%). At discharge, 26.2% of the patients had a poor outcome (mRS>2), and at the one-month follow-up, 14.3% of the patients had a poor outcome. The only independent predictor for poor outcomes of PRES was the presence of diffusion restriction on MRI. Conclusion: This study would enhance our understanding of PRES’s nature in our context. However, prospective large-scale multicenter studies are necessary to establish factors that are independently associated with unfavourable outcomes in PRES. JCMCTA 2023 ; 34 (2) : 25-30